Childhood bronchiolitis obliterans in Hong Kong‐case series over a 20‐year period. Issue 1 (24th November 2020) - Chan, Kate C.; Yu, Michelle W.; Cheung, Tammy W. Y.; Lam, David S. Y.; Leung, Theresa N. H.; Tsui, Tak K.; Ip, Ka I.; Chau, Christy S. K.; Lee, So L.; Yip, Ada Y. F.; Wong, Tak W.; Mak, Vivien C. W.; et al.
Abstract: Background and Objective: Bronchiolitis obliterans (BO) is a rare but serious condition. The natural history and outcomes remain poorly understood. In this clinical review, we aimed to describe the clinical characteristics and outcomes of children diagnosed with BO in Hong Kong (HK). Methods: This was a retrospective study of pediatric patients with BO under the care of six respiratory units in HK from January 1996 to December 2015. Information was retrieved from medical records. Results: Fifty‐six patients were included with a male predominance (67.9%). The median age at diagnosis was 1.98 years (interquartile range [IQR]: 0.84–4.99 years). Postinfectious BO (PIBO) was the commonest cause (64.3%) followed by posthematopoietic stem‐cell transplant (21.4%). Adenovirus (63.2%) was the commonest causative pathogen among PIBO. The median follow‐up duration was 9.7 years (IQR: 2.9–14.3 years). Twenty‐five patients (44.6%) could achieve symptom‐free recovery at the time of follow‐up. Five (8.9%) and three (5.4%) were oxygen or ventilator dependent, respectively. There were two deaths, both had posttransplant BO. Patients who developed BO after transplant had significantly worse lung function than those with PIBO. There were no risk factors significantly associated with worse clinical outcomes (oxygen/ventilator dependence or death) by logistic regression. Among patients with PIBO, coinfection at presentation was significantly associated with persistent symptoms at follow‐up ( p = .028). Conclusions: The most common cause of childhood BO in HK is postinfectious and coinfection at presentation was associated with persistent symptoms at follow‐up. Further studies are needed to better elucidate disease progression, treatment options and long term outcomes.